The Canadian-Mexico Commodity Trade and Exchange Rate Uncertainty: An Asymmetric Analysis - Bahmani-Oskooee, Mohsen; Harvey, Hanafiah (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2023)
A previous study assessed asymmetric effects of the real peso-dollar volatility on trade flows between Mexico and the U.S., two members of the former NAFTA. We now expand that analysis by considering the trade flows between Mexico and Canada. Estimating traditional linear models did not yield much significant effects of the real peso-Canadian dollar volatility on trade flows between the two countries. However, estimating a nonlinear model revealed that four out of 16 Canadian exporting industries to Mexico and 10 out of 21 Mexican industries to Canada were affected asymmetrically. While the export shares of four Canadian industries was 28.2%, that of 10 Mexican industries, with a non-linear model was 80%. Additionally, while increased volatility boosted exports of four US industries, it had no significant effects on the exports of 10 Mexican industries. In contrast, decreased volatility had no significant effects on the US exporting industries, but it had favorable impact on Mexican exporting industries.